Oligomers of Cyclic Oligochalcogenides for Enhanced Cellular Uptake. (6th November 2020) - Martinent, Rémi; Du, Dongchen; López‐Andarias, Javier; Sakai, Naomi; Matile, Stefan
Abstract: Monomeric cyclic oligochalcogenides (COCs) are emerging as attractive transporters to deliver substrates of interest into the cytosol through thiol‐mediated uptake. The objective of this study was to explore COC oligomers. We report a systematic evaluation of monomers, dimers, and trimers of asparagusic, lipoic, and diselenolipoic acid as well as their supramolecular monomers, dimers, trimers, and tetramers. COC dimers were more than twice as active as the monomers on both the covalent and noncovalent levels, whereas COC trimers were not much better than dimers. These trends might suggest that thiol‐mediated uptake of COCs is synergistic over both short and long distances, that is, it involves more than two COCs and more than one membrane protein, although other interpretations cannot be excluded at this level of complexity. These results thus provide attractive perspectives for structural evolution as well as imminent use in practice. Moreover, they validate automated HC‐CAPA as an invaluable method to collect comprehensive data on cytosolic delivery within a reasonable time at a level of confidence that is otherwise inconceivable. Abstract : Cumulated synergism in COC dimers of dimers : Efficient thiol‐mediated cytosolic delivery with monomeric COCs (cyclic oligochalcogenides) called for the introduction of COC oligomers. The results from a comprehensive collection of trifunctional monomers, dimers and trimers of asparagusic, lipoic and diselenolipoic acid imply that in the best COC oligomers, COCs might work together, over short and long distances.